A cobalt-free layered material with cation defects combined with aluminum doping, preparation method thereof, and application in lithium batteries

By introducing cationic defects and aluminum doping into the cathode material of lithium-ion batteries and replacing Co, a low-cost cobalt-free layered material was developed, which solved the problem of high Co cost and improved the performance and economicality of the material.

CN115911312BActive Publication Date: 2025-02-18NINGXIA UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211438811.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-17
Publication Date
2025-02-18
Estimated Expiration
2042-11-17

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials contain Co, which leads to high costs and limits the widespread application of materials in the electric vehicle field.

Method used

The cobalt-free layered material with cationic defects combined with aluminum doping is used, and the chemical formula is LiNixMnyAlzO2. By introducing cationic vacancy and aluminum doping, it replaces Co in traditional NMC materials and reduces costs.

Benefits of technology

While maintaining the same discharge capacity as the NMC, the cost of the material is significantly reduced and the voltage operating range, lithium ion conductivity, Coulomb efficiency and cycling stability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115911312B_ABST
    Figure CN115911312B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of battery materials, and specifically relates to a cobalt-free layered material with cation defects combined with aluminum doping, a preparation method thereof, and an application in lithium batteries. The cobalt-free layered material provided by the present invention has a chemical formula as shown in Formula 1: LiNi x Mn y Al z O2 formula 1; in formula 1: x+y+z<1. The material provided by the present invention retains the high capacity of nickel, and reduces the migration barrier of lithium ions in the material through cation vacancy defects, which is beneficial to the transportation of lithium ions; the crystal structure of the material during the charging and discharging process is made more stable by aluminum doping, thereby improving the cycle stability of the material. Therefore, the material provided by the present invention not only achieves the significant advantages of having a higher voltage operating range and low cost while maintaining the same discharge capacity as NMC. Moreover, the cobalt-free layered material provided by the present invention has higher lithium ion conductivity, higher coulombic efficiency and cycle stability compared with NM positive electrode materials and NMA positive electrode materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a cation defect combined with aluminum doping cobalt-free layered material, a preparation method thereof, and application in lithium batteries. Background Art

[0002] Lithium-ion batteries are a new generation of secondary batteries developed on the basis of lithium primary batteries. They are widely used in small portable electronic communication products and electric vehicles. The main positive electrode materials of lithium-ion batteries that have been industrialized are lithium cobalt oxide, modified lithium manganese oxide, lithium iron phosphate, ternary materials, etc. Although lithium cobalt oxide has stable performance, it is expensive and the cobalt element is toxic, which may cause environmental pollution. Although spinel lithium manganese oxide is cheap, it has a Jahn-Teller effect that leads to poor cycle performance, and its electrochemical performance decays rapidly at high temperatures due to the dissolution of manganese. Lithium iron phosphate has poor conductivity, poor batch quality, poor low-temperature performance, and there is a problem that the dissolution of trace iron may cause battery short circuit. Therefore, studies have found that LiNi x Co y Mn 1-x-y The layered nickel cobalt manganese oxide series materials (referred to as ternary materials) represented by O2 (NMC, x+y+z=1) have the advantages of the above materials and make up for the shortcomings of lithium cobalt oxide, modified lithium manganese oxide and lithium iron phosphate to a certain extent. It has the characteristics of high specific capacity, stable cycle performance, relatively low cost and good safety performance.

[0003] However, NMC materials still contain Co. With the development of the electric vehicle field, the high price of Co has increasingly become a bottleneck restricting the widespread application of NMC materials. Summary of the invention

[0004] The purpose of the present invention is to provide a cation defect combined with aluminum doping cobalt-free layered material and a preparation method thereof and application in a lithium battery. The cation defect combined with aluminum doping cobalt-free layered material provided by the present invention has a significant advantage of low cost while maintaining the same discharge capacity as NMC.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a cobalt-free layered material with cation defects combined with aluminum doping, the chemical formula of which is shown in Formula 1: LiNi x Mn y Al z O2 formula 1;

[0007] In formula 1: x+y+z<1.

[0008] Preferably, in Formula 1: 0.33≤x≤0.96; 0.01≤z≤0.33.

[0009] Preferably, the chemical formula of the cation-deficient combined aluminum-doped cobalt-free layered material is LiNi 0.8 Mn 0.1125 Al 0.05 O2、LiNi 0.8 Mn 0.135 Al 0.02 O2 or LiNi 0.8 Mn 0.03 Al 0.16 O2.

[0010] The present invention provides a method for preparing the cation-deficient aluminum-doped cobalt-free layered material described in the above technical solution, comprising the following steps:

[0011] According to the stoichiometric ratio of Ni element, Mn element and Al element in the chemical formula shown in Formula 1, a nickel source, an aluminum source, a manganese source and LiOH are mixed to obtain a mixture;

[0012] The mixed material is heated and calcined to obtain an initial layered material; the calcination temperature is ≥ the melting point of LiOH;

[0013] The initial layered material is annealed in an oxygen atmosphere to obtain the cobalt-free layered material with the cation defects combined with aluminum doping.

[0014] Preferably, the total amount of nickel in the nickel source, aluminum in the aluminum source and manganese in the manganese source to the amount of LiOH is 1:(4-8).

[0015] Preferably, the calcination temperature is ≥700° C. and < the boiling point of LiOH, and the calcination holding time is 8 to 24 hours.

[0016] Preferably, the heating rate from room temperature to the calcination temperature is 0.1-20° C. / min.

[0017] Preferably, the temperature of the annealing treatment is 400-600° C.; and the holding time of the annealing treatment is 4-24 hours.

[0018] Preferably, the heating rate from room temperature to the annealing temperature is 0.1-20° C. / min.

[0019] The present invention provides the use of the cation defect combined with aluminum doping cobalt-free layered material described in the above technical solution or the cation defect combined with aluminum doping cobalt-free layered material prepared by the preparation method described in the above technical solution as a positive electrode material for a lithium ion battery.

[0020] The present invention provides a cobalt-free layered material with cation defects combined with aluminum doping, the chemical formula of which is shown in Formula 1: LiNi x Mn y Al z O2 formula 1; in formula 1: x+y+z<1. The cobalt-free layered material provided by the present invention replaces the traditional layered positive electrode material LiNi with trivalent Al atoms. x Mn y Co z O2 (NMC, x+y+z=1) material, and at the same time introduce cation vacancies to obtain a cobalt-free layered material combining cation defects with aluminum doping. The material provided by the present invention retains the high capacity of nickel, and reduces the migration barrier of lithium ions in the material through cation vacancy defects, which is beneficial to the transportation of lithium ions; aluminum doping makes the crystal structure of the material more stable during the charging and discharging process, thereby improving the cyclic stability of the material. Therefore, the material provided by the present invention not only achieves the significant advantages of having a higher voltage operating range and low cost while maintaining the same discharge capacity as NMC. Moreover, the cobalt-free layered material (denoted as NMA-D) provided by the present invention is different from the cobalt-free LiNi x Mn 1-x O2(NM, x≥0.5) cathode materials and cobalt-free LiNi x Mn y Al z Compared with O2 (NMA, x+y+z=1) positive electrode material, it has higher lithium ion conductivity, higher coulombic efficiency and cycle stability.

[0021] The present invention provides a method for preparing a cobalt-free layered material with cation defects combined with aluminum doping as described in the above technical solution, comprising the following steps: according to the stoichiometric ratio of Ni, Mn and Al in the chemical formula shown in Formula 1, a nickel source, an aluminum source, a manganese source and LiOH are mixed to obtain a mixture; the mixture is heated and calcined to obtain an initial layered material; the calcination temperature is ≥ the melting point of LiOH; the initial layered material is annealed in an oxygen atmosphere to obtain the cation defect combined with aluminum doped cobalt-free layered material. The preparation method provided by the present invention uses LiOH as both a lithium source and a molten salt medium, and feeds materials according to the stoichiometric ratio of Ni, Mn and Al in the chemical formula shown in Formula 1, and directly synthesizes an initial layered material doped with Al with cation vacancy defects by a molten salt method, and then completely oxidizes the nickel ions in the initial layered material to trivalent nickel by annealing in an oxygen atmosphere, thereby inhibiting Li + / Ni 2+ The preparation method provided by the invention is simple, low in cost and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 LiNi prepared in Example 1 of the present invention 0.8 Mn 0.1125 Al 0.05 XRD pattern of O2 material;

[0023] Figure 2 LiNi prepared in Example 1 of the present invention 0.8 Mn 0.1125 Al 0.05 The lithium ion diffusion coefficient of O2 material changes with the working voltage;

[0024] Figure 3 LiNi prepared in Example 1 of the present invention 0.8 Mn 0.1125 Al 0.05 Curve of the coulombic efficiency of O2 material changing with the number of cycles;

[0025] Figure 4 LiNi prepared in Example 1 of the present invention 0.8 Mn 0.1125 Al 0.05 Electron microscope photo of O2 material;

[0026] Figure 5 LiNi prepared in Example 2 of the present invention 0.8 Mn 0.135 Al 0.02 XRD pattern of O2 material;

[0027] Figure 6 LiNi prepared in Example 2 of the present invention 0.8 Mn 0.135 Al 0.02 The lithium ion diffusion coefficient of O2 material changes with the working voltage;

[0028] Figure 7 LiNi prepared in Example 2 of the present invention 0.8 Mn 0.135 Al 0.02 Curve of the coulombic efficiency of O2 material changing with the number of cycles;

[0029] Figure 8 LiNi prepared in Example 3 of the present invention 0.8 Mn 0.03 Al 0.16 XRD pattern of O2 material;

[0030] Fig. 9 LiNi prepared in Example 3 of the present invention 0.8 Mn 0.03 Al 0.16The lithium ion diffusion coefficient of O2 material changes with the working voltage;

[0031] Fig.10 LiNi prepared in Example 3 of the present invention 0.8 Mn 0.03 Al 0.16 Curve of the coulombic efficiency of O2 material changing with the number of cycles;

[0032] Fig.11 LiNi prepared in Comparative Example 1 of the present invention 0.8 Mn 0.1 Co 0.1 The lithium ion diffusion coefficient of O2 (denoted as NMC811) material changes with the operating voltage;

[0033] Fig.12 LiNi prepared in Comparative Example 1 of the present invention 0.8 Mn 0.1 Co 0.1 The coulombic efficiency of O2 (denoted as NMC811) changes with the number of cycles;

[0034] Fig.13 LiNi prepared in Comparative Example 2 of the present invention 0.8 Mn 0.2 The lithium ion diffusion coefficient of O2 (denoted as NM82) material changes with the operating voltage;

[0035] Fig.14 LiNi prepared in Comparative Example 2 of the present invention 0.8 Mn 0.2 The coulombic efficiency of O2 (denoted as NM82) material changes with the number of cycles;

[0036] Fig.15 LiNi prepared in Comparative Example 3 of the present invention 0.8 Mn 0.15 Al 0.05 The lithium ion diffusion coefficient of O2 (denoted as NMA805) material changes with the operating voltage;

[0037] Fig.16 LiNi prepared in Comparative Example 3 of the present invention 0.8 Mn 0.15 Al 0.05 The coulombic efficiency curve of O2 (denoted as NMA805) material changes with the number of cycles. DETAILED DESCRIPTION

[0038] The present invention provides a cobalt-free layered material with cation defects combined with aluminum doping, the chemical formula of which is shown in Formula 1: LiNi x Mn y Alz O2 formula 1;

[0039] In formula 1: x+y+z<1.

[0040] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.

[0041] In the present invention, in Formula 1: 0.33≤x≤0.96; 0.01≤z≤0.33.

[0042] In the present invention, the chemical formula of the cation defect combined with aluminum-doped cobalt-free layered material is preferably LiNi 0.8 Mn 0.1125 Al 0.05 O2、LiNi 0.8 Mn 0.135 Al 0.02 O2 or LiNi 0.8 Mn 0.03 Al 0.16 O2.

[0043] In the present invention, the cation-deficient cobalt-free layered material combined with aluminum doping is of a rhombic α-NaFeO2 structural type, and the space group is R-3m.

[0044] In the present invention, the cation-deficient combined aluminum-doped cobalt-free layered material is free of impurity phases.

[0045] The present invention provides a method for preparing the cation-deficient aluminum-doped cobalt-free layered material described in the above technical solution, comprising the following steps:

[0046] According to the stoichiometric ratio of Ni element, Mn element and Al element in the chemical formula shown in Formula 1, a nickel source, an aluminum source, a manganese source and LiOH are mixed to obtain a mixture;

[0047] The mixed material is heated and calcined to obtain an initial layered material; the calcination temperature is ≥ the melting point of LiOH;

[0048] The initial layered material is annealed in an oxygen atmosphere to obtain the cobalt-free layered material with the cation defects combined with aluminum doping.

[0049] According to the present invention, a nickel source, an aluminum source, a manganese source and LiOH are mixed according to the stoichiometric ratio of the Ni element, the Mn element and the Al element in the chemical general formula shown in Formula 1 to obtain a mixed material.

[0050] In the present invention, the nickel source is preferably Ni(NO3)2·6H2O.

[0051] In the present invention, the aluminum source is preferably Al(NO3)3·9H2O.

[0052] In the present invention, the manganese source is preferably Mn(NO3)2.

[0053] In the present invention, the Mn(NO3)2 is preferably a purchased Mn(NO3)2 aqueous solution with a mass percentage of 50%.

[0054] In the present invention, the Mn(NO3)2 raw material is preferably purchased from McLean, manganese nitrate solution, AR, 50wt.%inH2O, CAS No.: 10377-66-9, MDL No.: MFCD00011112.

[0055] In the present invention, the total amount ratio of the nickel element in the nickel source, the aluminum element in the aluminum source and the manganese element in the manganese source to the amount of LiOH is preferably 1:(4-8), more preferably 1:4.

[0056] In the present invention, the mixed raw materials preferably also include water, and the water is preferably deionized water.

[0057] In the present invention, the mixed raw materials preferably also include water, and the mixing preferably includes the following steps: first mixing the nickel source, aluminum source, manganese source and water to obtain a metal salt mixture; second mixing the metal salt mixture and the LiOH to obtain an initial mixture; drying the initial mixture to obtain the mixture. In the present invention, the first mixing is preferably carried out under stirring conditions, and the stirring is preferably magnetic stirring. In the present invention, the second mixing is preferably carried out under stirring conditions. In the present invention, the drying temperature is preferably 200°C, the drying is preferably oven drying, and the drying is preferably carried out in a bellows. The present invention preferably achieves uniform mixing of the three metal salts through the first mixing. The present invention preferably adds water during the mixing process to improve the mixing uniformity of the nickel source, aluminum source, manganese source and LiOH.

[0058] After obtaining the mixed material, the present invention heats the mixed material for calcination to obtain an initial layered material; the calcination temperature is ≥ the melting point of the LiOH.

[0059] In the present invention, the calcination temperature is preferably ≥ 700° C. and < the boiling point of LiOH, and more preferably 700° C. In the present invention, the calcination holding time is preferably 8 to 24 hours, and more preferably 8 to 12 hours.

[0060] In the present invention, the heating rate from room temperature to the calcination temperature is preferably 0.1 to 20° C. / min, more preferably 1 to 5° C. / min, and further preferably 3° C. / min.

[0061] In the present invention, the calcination is preferably carried out in a muffle furnace.

[0062] During the calcination, LiOH is used as a lithium source and a molten salt medium at the same time. At the calcination temperature, the LiOH melts into a liquid state, and the nickel source, aluminum source, manganese source and liquid LiOH react to obtain an initial layered material.

[0063] In the present invention, a calcined product is obtained after the calcination is completed. In the present invention, the calcined product is preferably subjected to post-treatment to obtain the initial layered material. In the present invention, the post-treatment preferably includes the following steps: cooling the calcined product, washing with water and performing solid-liquid separation in sequence to obtain a solid phase product; drying the solid phase product to obtain the initial layered material. In the present invention, the cooling is preferably: after the calcination is completed, the calcined product is immediately transferred to an iron sheet for rapid cooling. In the present invention, the unreacted LiOH in the calcined product is preferably washed away by water. In the present invention, the solid-liquid separation is preferably filtration. In the present invention, the drying temperature is preferably 100°C, the drying is preferably carried out in a drying oven, and the drying insulation time is preferably overnight.

[0064] After obtaining the initial layered material, the present invention performs annealing treatment on the initial layered material in an oxygen atmosphere to obtain the cation defect combined with aluminum doping cobalt-free layered material.

[0065] In the present invention, before the annealing, the initial layered material is preferably ground to obtain an initial layered material powder. The present invention preferably performs the annealing treatment on the initial layered material powder.

[0066] In the present invention, the annealing temperature is preferably 400-600° C., more preferably 500-600° C., and even more preferably 500° C. In the present invention, the annealing holding time is preferably 4-24 hours, more preferably 12-15 hours, and even more preferably 12 hours.

[0067] In the present invention, the heating rate from room temperature to the annealing temperature is preferably 0.1 to 20° C. / min, more preferably 1 to 5° C. / min, and further preferably 3° C. / min.

[0068] In the present invention, an annealing product is obtained after the annealing treatment. In the present invention, the annealing product is preferably post-treated to obtain the cation defect combined with aluminum-doped cobalt-free layered material. In the present invention, the post-treatment preferably includes the following steps: washing the returned product with water, filtering and drying in sequence. In the present invention, the solid-liquid separation is preferably filtration. In the present invention, the drying temperature is preferably 100°C, the drying is preferably carried out in a drying oven, and the drying insulation time is preferably overnight.

[0069] The present invention provides the use of the cation defect combined with aluminum doping cobalt-free layered material described in the above technical solution or the cation defect combined with aluminum doping cobalt-free layered material prepared by the preparation method described in the above technical solution as a positive electrode material for a lithium ion battery.

[0070] In order to further illustrate the present invention, the technical solution provided by the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0071] Example 1

[0072] 4.653 g Ni(NO3)2·6H2O, 0.375 g Al(NO3)3·9H2O, and 0.805 g Mn(NO3)2 (the mass percentage of Mn(NO3)2 is 50%) were dissolved in 20 mL deionized water and stirred evenly on a magnetic stirrer. LiOH (4 times the total mass of the nickel element in the nickel source, the aluminum element in the aluminum source, and the manganese element in the manganese source) was weighed and added, and stirred again. The mixed solution was then placed on a 2 The NMA material was dried in a bellows at 00°C, and then heated to 700°C at a rate of 3°C / min in a muffle furnace and kept warm for 8 hours. After the insulation, it was immediately transferred to an iron sheet for rapid cooling, washed with water after cooling, filtered, and dried in a drying oven at 100°C overnight; the dried NMA material was ground in an agate mortar, and then heated to 500°C at a rate of 3°C / min in a tubular furnace in an oxygen atmosphere and kept warm for 12 hours, washed with water again, filtered and dried to obtain LiNi 0.8 Mn 0.1125 Al 0.05 O2.

[0073] Figure 1 LiNi prepared in Example 1 of the present invention 0.8 Mn 0.1125 Al 0.05 XRD spectrum of O2 material. It can be concluded from the XRD spectrum that the product prepared by the present invention has a layered structure.

[0074] Figure 2 LiNi prepared in Example 1 of the present invention 0.8 Mn0.1125 Al 0.05 The lithium ion diffusion coefficient of O2 material changes with the working voltage; Figure 3 LiNi prepared in Example 1 of the present invention 0.8 Mn 0.1125 Al 0.05 The coulombic efficiency of O2 material changes with the number of cycles; Figure 2 and Figure 3 It can be concluded that the LiNi prepared by the present invention 0.8 Mn 0.1125 Al 0.05 The degree of Li / Ni mixing in O2 is relatively light; the large value of lithium ion diffusion coefficient indicates that lithium ions diffuse relatively easily, and gradually decrease with the progress of charge state, and the coulomb efficiency has been maintained at a high value (about 99%) from the beginning.

[0075] Figure 4 LiNi prepared in Example 1 of the present invention 0.8 Mn 0.1125 Al 0.05 Electron microscope photo of O2 material: Figure 4 It can be concluded that the LiNi prepared by the present invention 0.8 Mn 0.1125 Al 0.05 The O2 particle size is uniform.

[0076] Example 2

[0077] 4.653 g Ni(NO3)2·6H2O, 0.15 g Al(NO3)3·9H2O, and 0.966 g Mn(NO3)2 (the mass percentage of Mn(NO3)2 is 50%) were dissolved in 20 mL deionized water and stirred evenly on a magnetic stirrer. LiOH (4 times the total mass of the nickel element in the nickel source, the aluminum element in the aluminum source, and the manganese element in the manganese source) was weighed and added, and stirred again. The mixed solution was then placed in a 20 The NMA material was dried in a 0°C wind box, and after drying, the temperature was increased to 700°C at a rate of 3°C / min in a muffle furnace and kept for 8 hours. After the insulation, it was immediately transferred to an iron sheet and cooled rapidly. After cooling, it was washed with water, filtered, and dried in a drying oven at 100°C overnight. The dried NMA material was ground in an agate mortar, and after grinding, the temperature was increased to 500°C at a rate of 3°C / min in a tubular furnace in an oxygen atmosphere and kept for 12 hours, and then washed with water again, filtered and dried to obtain LiNi 0.8 Mn 0.135 Al 0.02 O2.

[0078] Figure 5 LiNi prepared in Example 2 of the present invention 0.8 Mn 0.135 Al0.02 XRD pattern of O2 material;

[0079] Figure 6 LiNi prepared in Example 2 of the present invention 0.8 Mn 0.135 Al 0.02 The lithium ion diffusion coefficient of O2 material changes with the working voltage; Figure 7 LiNi prepared in Example 2 of the present invention 0.8 Mn 0.135 Al 0.02 The coulombic efficiency of O2 material changes with the number of cycles; Figure 6 and Figure 7 It can be concluded that the LiNi prepared in this embodiment 0.8 Mn 0.135 Al 0.02 The degree of Li / Ni mixing in the O2 material increases with the decrease of Al content, the lithium ion diffusion coefficient decreases slightly compared with Example 1, the initial Coulomb efficiency is low, and gradually increases and then decreases with the increase of cycle number.

[0080] Example 3

[0081] 4.653 g Ni(NO3)2·6H2O, 1.2 g Al(NO3)3·9H2O, and 0.215 g Mn(NO3)2 (the mass percentage of Mn(NO3)2 is 50%) were dissolved in 20 mL deionized water and stirred evenly on a magnetic stirrer. LiOH (4 times the total mass of the nickel element in the nickel source, the aluminum element in the aluminum source, and the manganese element in the manganese source) was weighed and added, and stirred again. The mixed solution was then placed in a 20 The NMA material was dried in a 0°C wind box, and after drying, the temperature was increased to 700°C at a rate of 3°C / min in a muffle furnace and kept for 8 hours. After the insulation, it was immediately transferred to an iron sheet and cooled rapidly. After cooling, it was washed with water, filtered, and dried in a drying oven at 100°C overnight. The dried NMA material was ground in an agate mortar, and after grinding, the temperature was increased to 500°C at a rate of 3°C / min in a tubular furnace in an oxygen atmosphere and kept for 12 hours, and then washed with water again, filtered and dried to obtain LiNi 0.8 Mn 0.03 Al 0.16 O2.

[0082] Figure 8 LiNi prepared in Example 3 of the present invention 0.8 Mn 0.03 Al 0.16 XRD pattern of O2 material.

[0083] Fig. 9 LiNi prepared in Example 3 of the present invention 0.8 Mn0.03 Al 0.16 The lithium ion diffusion coefficient of O2 material changes with the working voltage; Fig.10 LiNi prepared in Example 3 of the present invention 0.8 Mn 0.03 Al 0.16 The coulombic efficiency of O2 material changes with the number of cycles; Fig. 9 and Fig.10 It can be concluded that the LiNi prepared in this embodiment 0.8 Mn 0.03 Al 0.16 The degree of Li / Ni mixing in O2 material is inhibited to a certain extent with the increase of Al content; the lithium ion diffusion coefficient is very low; the early coulomb efficiency is lower than that of Experimental Example 2, but it has an upward trend with the increase of the number of cycles.

[0084] Comparative Example 1

[0085] 4.653 g Ni(NO3)2·6H2O, 0.366 g Co(NO3)2·6H2O, and 0.716 g Mn(NO3)2 (the mass percentage of Mn(NO3)2 is 50%) were dissolved in 20 mL deionized water and stirred evenly on a magnetic stirrer. LiOH in an amount 4 times the total amount of the nickel element in the nickel source, the cobalt element in the cobalt source, and the manganese element in the manganese source was weighed and added, and stirred again. The mixed solution was then placed on a 2 The NMC was dried in a bellows at 00°C, and then heated to 700°C at a rate of 3°C / min in a muffle furnace and kept warm for 8 hours. After the insulation, it was immediately transferred to an iron sheet for rapid cooling, washed with water after cooling, filtered, and dried in a drying oven at 100°C overnight; the dried NMC material was ground in an agate mortar, and after grinding, it was heated to 500°C at a rate of 3°C / min in a tubular furnace in an oxygen atmosphere and kept warm for 12 hours, washed with water again, filtered and dried to obtain LiNi 0.8 Mn 0.1 Co 0.1 O2 (denoted as NMC811) material.

[0086] Fig.11 LiNi prepared in Comparative Example 1 of the present invention 0.8 Mn 0.1 Co 0.1 The lithium ion diffusion coefficient of O2 (denoted as NMC811) material changes with the operating voltage; Fig.12 LiNi prepared in Comparative Example 1 of the present invention 0.8 Mn 0.1 Co 0.1 The coulombic efficiency of O2 (denoted as NMC811) changes with the number of cycles; Fig.11 and Fig.12It can be concluded that the lithium ion diffusion coefficient of the NMC811 material prepared in this comparative example is not high, and the coulombic efficiency gradually becomes unstable after a certain number of cycles.

[0087] Comparative Example 2

[0088] 4.653gNi(NO3)2·6H2O and 1.432gMn(NO3)2 raw materials (the mass percentage of Mn(NO3)2 is 50%) are dissolved in 20mL deionized water, stirred evenly on a magnetic stirrer, and LiOH in an amount of 4 times the total amount of the nickel element in the nickel source and the manganese element in the manganese source is weighed and added, stirred again, and then the mixed solution is placed in a 200°C wind box for drying, and after drying, the temperature is increased to 700°C at a rate of 3°C / min in a muffle furnace and kept warm for 8h, and after the insulation is completed, it is immediately transferred to an iron sheet for rapid cooling, and after cooling, it is washed with water, filtered, and dried in a drying oven at 100°C overnight; the dried NM material is ground in an agate mortar, and after grinding, it is heated to 500°C at a rate of 3°C / min in a tubular furnace in an oxygen atmosphere and kept warm for 12h, washed with water again, filtered and dried to obtain LiNi 0.8 Mn 0.2 O2 (referred to as NM82 material).

[0089] Fig.13 LiNi prepared in Comparative Example 2 of the present invention 0.8 Mn 0.2 The lithium ion diffusion coefficient of O2 (denoted as NM82) material changes with the operating voltage; Fig.14 LiNi prepared in Comparative Example 2 of the present invention 0.8 Mn 0.2 The coulombic efficiency of O2 (denoted as NM82) changes with the number of cycles; Fig.13 and Fig.14 It can be concluded that the LiNi prepared in this comparative example 0.8 Mn 0.03 Al 0.16 The Li ion diffusivity of O2 material is low and the Coulomb efficiency is low.

[0090] Comparative Example 3

[0091] 4.653 g Ni(NO3)2·6H2O, 1.074 g Mn(NO3)2 raw material (the mass percentage of Mn(NO3)2 is 50%), and 0.375 g Al(NO3)3·9H2O are dissolved in 20 mL deionized water, and stirred evenly on a magnetic stirrer. LiOH in an amount 4 times the total amount of the nickel element in the nickel source, the aluminum element in the aluminum source, and the manganese element in the manganese source is weighed and added, and stirred again. The mixed solution is then placed on a 2 The NMA material was dried in a bellows at 00°C, and then heated to 700°C at a rate of 3°C / min in a muffle furnace and kept warm for 8 hours. After the insulation, it was immediately transferred to an iron sheet for rapid cooling, washed with water after cooling, filtered, and dried in a drying oven at 100°C overnight; the dried NMA material was ground in an agate mortar, and then heated to 500°C at a rate of 3°C / min in a tubular furnace in an oxygen atmosphere and kept warm for 12 hours, washed with water again, filtered and dried to obtain LiNi 0.8 Mn 0.15 Al 0.05 O2 (referred to as NMA805 material).

[0092] Fig.15 LiNi prepared in Comparative Example 3 of the present invention 0.8 Mn 0.15 Al 0.05 The lithium ion diffusion coefficient of O2 (denoted as NMA805) material changes with the operating voltage; Fig.16 LiNi prepared in Comparative Example 3 of the present invention 0.8 Mn 0.15 Al 0.05 The coulombic efficiency of O2 (denoted as NMA805) material changes with the number of cycles. Fig.15 and Fig.16 It can be concluded that the NMA805 material prepared in this comparative example has a lower initial coulombic efficiency, but as the cycle proceeds, the coulombic efficiency gradually increases.

[0093] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A cobalt-free layered material with cation defects combined with aluminum doping, the chemical formula of which is shown in Formula 1: LiNi 0.8 Mn 0.1125 Al 0.05 O2 formula 1.

2. The method for preparing the cation-deficient aluminum-doped cobalt-free layered material according to claim 1, characterized in that: The following steps are involved: According to the stoichiometric ratio of Ni element, Mn element and Al element in the chemical formula shown in Formula 1, a nickel source, an aluminum source, a manganese source and LiOH are mixed to obtain a mixture; The mixed material is heated and calcined to obtain an initial layered material; the calcination temperature is ≥ the melting point of LiOH; The initial layered material is annealed in an oxygen atmosphere to obtain the cobalt-free layered material with the cation defects combined with aluminum doping.

3. The preparation method according to claim 2, characterized in that: The total amount of nickel in the nickel source, aluminum in the aluminum source and manganese in the manganese source to the amount of LiOH is 1:(4-8).

4. The preparation method according to claim 2, characterized in that: The calcination temperature is ≥700°C and < the boiling point of LiOH, and the calcination holding time is 8 to 24 hours.

5. The preparation method according to claim 4, characterized in that: The heating rate from room temperature to the calcination temperature is 0.1-20°C / min.

6. The preparation method according to claim 2, characterized in that: The temperature of the annealing treatment is 400-600° C.; the holding time of the annealing treatment is 4-24 hours.

7. The preparation method according to claim 6, characterized in that: The heating rate from room temperature to the annealing temperature is 0.1-20° C. / min.

8. Use of the cation-deficient combined aluminum-doped cobalt-free layered material according to claim 1 or the cation-deficient combined aluminum-doped cobalt-free layered material prepared by the preparation method according to any one of claims 2 to 7 as a positive electrode material for lithium-ion batteries.

Citation Information

Patent Citations

  • Modified lithium nickel manganese oxide material, preparation method thereof, and lithium ion battery containing material

    CN103236539A

  • Positive electrode active material, and lithium battery containing positive electrode active material

    JP2015022958A